CRY PROTEINS FROM Bacillus thuringiensis: FROM NATURAL INSECTICIDE TO BIOTECHNOLOGICAL TOOL FOR AGRICULTURAL PEST CONTROL (Agro Productividad, 2026)
Objective: The Cry protein family from Bacillus thuringiensis (Bt) exhibits biocidal activity against various insect orders, with Lepidoptera being among their primary targets. These insects often evolve into major agricultural pests, leading to significant crop losses. Consequently, research efforts have focused on the identification and cloning of the genes encoding these proteins, as well as elucidating their mechanism of action.Design/Methodology/Approach: Methods for the identification, isolation, and purification of Cry proteins, along with the current state of the art, were explored, described, and discussed by reviewing relevant literature using scientific databases for bibliographic research.Results: Cry proteins constitute a diverse group  of molecules with demostrated activity for combating agricultural insect pests, primarily Lepidoptera. These proteins and their corresponding genes have been widely studied and  employed in the genetic transformation of several crop plant species.Limitations/Implications of the study: Although several models have been proposed to explain the mode of action of Cry proteins, molecular mechanism remain unresolved to fully understand their insecticidal activity.Findings/Conclusions: Bt encodes multiple groups of proteins with insecticidal activity, among which the Cry protein family is the most extensively studied. The identification of its first members, along with the elucidation of their three-dimensional structure, has been essential for proposing their mechanism of action. This has enabled the targeted control of several Lepidopteran pests in agriculture.